Performance study of adsorption cooling system driven by waste heat from automobile engine / Khairul Habib and Nurul Afiqah Kamaruzzaman - Habib, Khairul; Kamaruzzaman, Nurul Afiqah (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Adsorption cooling system driven by waste heat from automobile engine driven out through radiator is used as an alternatives means to drive adsorption cooling system. Air conditioning of lightweight vehicle has been considered in term of energy savings and environmental issues. This article presents an instantaneous modelling and performance analysis of the waste heat from automobile engine driven two-bed adsorption chiller employing water and silica gel as refrigerant and adsorbent, respectively. The effects of adsorption/desorption cycle time, regeneration and cooling water temperature on the performance are reported in terms of specific cooling capacity (SCC)and coefficient of performance (COP). Results indicate that the chiller is able to produce SCC of 15 kW and a COP of 0.5, even when the low-temperature (between 70°C and 90°C) heat source from engine waste heat is available.However, improvement is still needed on the coefficient of performance.Performance study of adsorption cooling system driven by waste heat from automobile engine